A 1911 Postcard of the National Hospital for the Paralysed and Epileptic Highlighting European Medical Specialty Training. Issue 1 (1st January 2017) - Zubair, Adeel; Boes, Christopher J.
Abstract : The purpose of this study was to describe the historical importance of a 1911 European hospital postcard sent from one American physician to another. In the late 19th and early 20th centuries, very few formal residency programs existed in America for training physicians. Most authors rightfully emphasize Johns Hopkins Hospital, founded in 1889, as the site of origin of the American medical residency, but these positions were for a chosen few. Many young physicians would go abroad to study medicine after completing medical school, a decision with many benefits and few drawbacks. At least 15, 000 Americans took some kind of medical training in Austria-Hungary, Germany, and Switzerland between 1870 and 1914. Dr. Frank F. Hutchins took such a trip to Europe. On March 12, 1911, Dr. Hutchins wrote a postcard from Queen Square, London, to Dr. Allison Maxwell admiring the positive attributes of The National Hospital for the Paralysed and Epileptic. This trip would serve to shape Dr. Hutchins' subsequent career and would influence the future of the Indiana University School of Medicine, neuropsychiatry in the US military, and the care of veterans.